Cancer Patients' Satisfaction with Nursing Care Provided in Teaching Hospitals in Tehran, Iran - Mehrnoosh Akhtari Zavare, (2007)

(untitled)
A cross-sectional study was conducted to determine cancer patients’ satisfaction level and factors that contribute to patients' satisfaction towards the nursing care services provided at the selected teaching hospitals in Tehran, Iran. A proportional stratified sampling method was adopted and data were collected via face-to-face interviews from November 2007 through January 2008, based on a validated Patient Satisfaction Questionnaire (PSQ). A total of 384 cancer patients aged 14 years old and above was selected. The majority of respondents were males (52.4%), married (66.4%) with age group 45-54 year (26.4%); secondary education level (44.8%). The majority of respondents was working adults (52.6%), with family monthly income of US$200-500 (60.9%), and hospitalized between 2 to 5 days (81.8%), and treated for chemotherapy (67.4 %). The findings revealed that a vast majority of these respondents (82.8%) was satisfied with the nursing care provided to them, while the others (17.2%) were not. Generally, most of the respondents were satisfied with the amount of information given by the nurses (76.6%), technical quality (76.8%), interpersonal relationship (96.6%) and physical environment (69.5%) they were admitted. From the bivariate analysis, only two factors were found to be significantly related to the level of satisfaction, i.e. the types of hospital (x2=4.985; df=1; p=0.025; n=384) and the types of treatment (x2=8.128; df=2; p=0.017; n=384). In term of the type of hospital, the multiple logistic regression test indicated that the patients, who were hospitalized in the teaching-hospitals of Shahis Beheshti University, were (1/0.523=1.912) times more likely to be satisfied with the nursing care (p= 0.037) as compared to those were hospitalized in the teaching-hospitals of Iran University. Similarly, the respondents who were married were 5.5 times more likely to be dissatisfied with the nursing care (p= 0.033) as compared to those who were divorced and widowed. The Nagelkerke R2 showed that about 14% of the variation in the level of the patients' satisfaction could be explained by this logistic model. This study found that most of the respondents were satisfied with the services which they received. However, the respondents suggested that several factors such as improving socio-environment in term of privacy and interpersonal manner in the care, and improving the facilities of the teaching-hospitals, should be taken into consideration in order to improve the overall satisfaction. At the same time, further research is still needed to study on the socio-cultural and environment pertaining to the issues of patient care in the teaching-hospitals. On the other hand the patients, admitted to Teachinghospitals of SHUMS, were more satisfied as compared to those admitted in the IUMS. Nevertheless, further research is also needed to find the reasons why those patients admitted to Teaching-hospitals of SHUMS had higher level of satisfaction, which also indicated the need to improve the interpersonal manners and socio-cultural aspects of patients' care.